Efficiency and Stability Ratios of the Transport Corporation Business - Zelenika, Ratko; Toković, Katarina (Promet - Traffic&Transportation, 2012)
Multidisciplinary character of traffic science in a widersense and science abouttransp01t in a narrower sense stipulatethe definition of semantic relation between the terms 'transpori'and 'traffic', as well as the meaning of conventional,combined and multimodal transpott, and some impottanttypes of traffic and transporl.Besides the definition of imporlant subjects about trafficand transp01t, for better understanding of the imparlance of financialratios of efficiency and stability for the transport corporationmanagement, the following are relevant facts of financialpolicy. This means the concept and imp01tance of financialpolicy which is composed of important subordinated policy.The most important objectives of financial policy areachieved by charging compensation for the given transp01t services.The compensation is determined based on tariffs as directconsequence of tariff policy.Successful deduction (derivation) of financial ratios of efficiencyand stability in the transporl corporation business requiresqualitative financial reporls, composed and processed insuch a way that they are adequate infO/mational basis for furtheruse.Imp01tant ratios of efficiency and stability deduced from financialreports oftransp011 corporation could be classified intothe following groups: liquidity, debt, activity, economy, profitabilityand investment ratios. Finally, standardised ratios deducedfrom adequately prepared financial rep011s could beused by the management oft he transp01t corporation as well asby other users.